Nexus Between Tourism Sector Output and Macroeconomic Indicators in Nigeria - Ajudua, Emmanuel I.; Majebi, Enesi C.; Odishika, Vivian A.; Bakare-Aremu, Tunde A.; Nwokoro, Athanasius; Fagbolu, Olukemi D. (Jurnal Ilmu Ekonomi Terapan, 2022)
Tourism has become one of the largest export industries worldwide and a key sector necessary for the socioeconomic growth of nations. Tourism's considerable and recognized roles as a foreign exchange earnings source, employment generation, and public income, amongst others, towards the growth of an economy have drawn much attention. The sector's performance is somewhat dependent on the macroeconomic variables in an economy. Thus, this study examines the relationship between tourism sector output and macroeconomic variables in Nigeria, covering the period 1991-2020. Tourism sector output proxied by tourism sector contribution to the GDP was employed as the dependent variable. At the same time, interest rate, foreign exchange and inflation rate, and money supply were the independent variables. The autoregressive distributed lag was employed to analyze data for the study. The ARDL's result cointegration test shows a long-run relationship between the variables employed, and a significant relationship exists between the dependent and independent variables. Based on the findings, the study recommends that interest rate, foreign exchange rate and inflation as they impact the tourism sector's performance. These variables tend to impact the tourism sector's performance and, as such, should be monitored and controlled.